CFD computation, analysis and design of a two-bladed wastewater pump - Litfin, Oliver; Mohr, Christian; Haddad, Kais; Epple, Philipp; Semel, Matthias; Becker, Klaus; Klein, Horst; Delgado, Antonio (ASME 2011 International Mechanical Engineering Congress and Exposition (IMECE 2011), 2011)
In this work a wastewater pump with a two-bladed prototype impeller and a specific speed of 0.68, referring to a wellestablished industrial design, was simulated in a commercial CFD solver, ANSYS CFX. Simulations of the impeller only and of the complete pump with spiral casing including a detailed analysis of the flow patterns were performed. A parameter study with around 25 new designs containing variations of the inlet angle and the wrap angle was carried out, leading to significant improvements of the flow pattern as well as of the hydraulic efficiency. Based on the optimum leading edge and wrap angle, the total head was improved by variation of the exit blade angle. Having set the better main dimensions, the effect of the blade shape, i.e. blade angle distribution, was investigated. Here it is shown that changing the blade angle distribution in such a way that the point of maximum blade angle is shifted to a bigger radius can lead to substantial improvements. One special focus in this whole study was also to describe and control the behavior of the relative eddy, which is directly related also to the slip factor. In the scope of this work it is shown how it is possible to influence and move the relative eddy to the best position, since due to the small relative velocities in the blade passage it is impossible to fully avoid it. A detailed analysis of these CFD results is presented as well as the recommendations for an efficient design of this special type of wastewater pump impellers. Copyright © 2011 by ASME.
UnivIS-Import:2017-11-07:Pub.2011.tech.ITC.stmmec.cfdcom